2018
DOI: 10.1186/s13059-018-1523-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel long noncoding RNA HOXC-AS3 mediates tumorigenesis of gastric cancer by binding to YBX1

Abstract: BackgroundRecently, increasing evidence shows that long noncoding RNAs (lncRNAs) play a significant role in human tumorigenesis. However, the function of lncRNAs in human gastric cancer remains largely unknown.ResultsBy using publicly available expression profiling data from gastric cancer and integrating bioinformatics analyses, we screen and identify a novel lncRNA, HOXC-AS3. HOXC-AS3 is significantly increased in gastric cancer tissues and is correlated with clinical outcomes of gastric cancer. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
196
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 238 publications
(208 citation statements)
references
References 44 publications
10
196
1
1
Order By: Relevance
“…Increasing evidences revealed that non‐coding RNAs, particularly lncRNAs and miRNAs, have considerable potential values in improving the diagnostic and therapeutic of GC . Researchers have found a large number of lncRNAs in GC development, such as lncRNA HOXC‐AS3, LINC01234 and lncRNA‐KRTAP5‐AS1 . Aberrantly expressed lncRNAs are involved in various malignant cytological behaviours of GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences revealed that non‐coding RNAs, particularly lncRNAs and miRNAs, have considerable potential values in improving the diagnostic and therapeutic of GC . Researchers have found a large number of lncRNAs in GC development, such as lncRNA HOXC‐AS3, LINC01234 and lncRNA‐KRTAP5‐AS1 . Aberrantly expressed lncRNAs are involved in various malignant cytological behaviours of GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…37,47 Studies have reported that YB1 can regulate proliferation and metastasis by binding to lncRNAs 37,47 or miRNAs, 48 and even demonstrate that YB1 effects EMT. 37,47 Studies have reported that YB1 can regulate proliferation and metastasis by binding to lncRNAs 37,47 or miRNAs, 48 and even demonstrate that YB1 effects EMT.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] A recent study reported that YBX1 participates in HOXC-AS3-mediated gene transcription, further regulating the tumorigenesis of gastric cancer. 30 However, the mechanism of HOXC-AS3 to regulate GBM cell progression is not clear, which requires further study and discussion.…”
Section: Discussionmentioning
confidence: 99%